Kajian Konsentrasi Pupuk Organik Cair Terhadap Pertumbuhan dan Hasil Jagung Manis (Zea mays saccarata L): POC, Kelinci, Kambing, Sapi, dosis, jagung manis - muryanto; Siswadi, Siswadi; Priyono, Priyono (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2023)
Research titled a study of the concentration to Liquid Organic Fertilizer (LOF) on the growth and fruit of sweet corn (Zea mays saccarata L.) and Implemented in strength Rt 3/Rw 6, The Town of Tohudan, and Colomadu districk, Karanganyar regency, Central Java province. Sweet corn research time in 30 December 2022 until 16 February 2023. This study aims to compare the effects of the administration of liquid organic manure rabbits, Organic Goat Pudding, and best liquid organic manure of cows against the growth of sweet corn plants (Zea mays saccarata L.). The experimental plan used is a random plan of complete group (CRBD) with single factor, There are 10 trial units each trial units repeated three times. Treatment used is without control treatment (k0), dose LOF of rabbit 40 ml / L of water (K1), LOF rabbit 40 ml / L of water (K2), LOF rabbit 60 ml / L water (K3), LOF goat 20 ml / L of water (K4), LOF goat 40 ml / L of water (K5), LOF goat 60 ml / l of water (K6), LOF cow 25 ml / l of water (K7), LOF cow 50 ml / L of water (K8 ), LOF cow 75 ml / L water (K9). Observation data is analyzed using different fingerprint analysis (ANOVA) and followed by bnt test at 1 %. Parameters observed include: height of plants, number of leaves, The diameter of the tray, The number of stitches, The number of unknowns, weight of the tray per plot, number of seed lines, The number of seats. Results of the study showed that the giving of LOF to rabbits, LOF to Goat, and LOF of cow have no effect on the growth and yield of sweet corn (Zea mays saccarata L.). Keywords: LOF, Rabbit, Goat, Cow, dosage, sweet corn